Quality and Pattern of Breakfast Through the GEMPITA PROGRAM at Palu City, Central Sulawesi - Ariany, Darma; Adhyanti, Adhyanti; Eka Cahyani, Yayuk; Hafid, Fahmi; Wahyuni, Rosa Dwi; Ngatimin, Dachruddin (Poltekkes Kemenkes Palu, 2023)
Many school-aged children in Indonesia still skip breakfast, which can have an impact on their learning concentration and academic performance at school. This study aims to describe the quality and pattern of breakfast through the GEMPITA Program at Palu City, Central Sulawesi. This was a descriptive study with a sample size of 228 elementary and junior high school students in Palu City. Data collection was performed through interviews using structured questionnaires and anthropometric measurements. The study results show that the majority of respondents had pocket money of more than IDR 5,000/day, came from families with fathers of senior high school graduates and non-civil servants, the mothers generally had primary and secondary education and were housewives. Furthermore, the majority of respondents had a routine breakfast habit by 57.9%, 20.2% had breakfast sometimes and 21.9% never had breakfast. Furthermore, only 32.9% had quality breakfast menu. Regarding snack consumption habit, the majority of respondents by 77.2% consumed snacks more than three times a week and more than half of respondents by 58.3% had the habit of bringing packed meal, while 41.7% never brought packed meal. An assessment of the nutritional status of respondents showed that there were still 33.3% who were undernourished and 7.9% who were over nourished and obese. Stunting status occurred in 18.9% of respondents. The breakfast habit, quality and pattern of elementary and high school students still need to be improved. The GEMPITA program is an alternative program to improve the pattern and quality of breakfast for elementary and high school-aged children in Palu City.